Siniša Kovačević’s The Conquest of the Homeland as a Serbian Story on the Post-war Migrations - Giergiel, Sabina (Porównania, 2022)
The paper’s aim is to pinpoint the popularity of Siniša Kovačević’s play Velika drama (Big Drama) in Serbia. In 2019 the play was published in a novel format as a family saga. It focuses on the Vučić family’s migration from remote and mountainous Montenegro to the Pannonian Basin. In this rather formulaic and idea-oriented text, Kovačević demonstrates that the post-war transfer of people is connected to the phenomenon of a “new human being” (who represents the traditional rural culture) arriving at Vojvodina, a region significantly better developed both economically and culturally. The article particularly concentrates on the picture of Montenegro and Vojvodina as presented in the novel. Kovačević’s method is to axiomatically modify these regions: Montenegro is the bulwark of old and authentic values, whereas Vojvodina signifies the other. This opposition is supplemented with the contradistinction of old age (associated with wisdom and tradition) and youth (identical with naivety and idealism).